Gaucher Disease: Clinical phenotypes and GBA1 variants spectrum in Kazakhstani patients - Amangeldiyeva, Aliya; Boranbayeva, Riza; Abdilova, Gulnara; Jaxybayeva, Indira; Akhmedova, Dilorom (Acta Biomedica Atenei Parmensis, 2026)
Background and Aim: Gaucher disease (GD) is a rare lysosomal storage disorder caused by mutations in the β-glucosidase (GBA1) gene, with more than 500 variants described. This study aimed to investigate the clinical features and spectrum of GBA1 variants in Kazakhstani patients with GD. Methods: Medical records from the national referral center for GD in Kazakhstan were reviewed. Forty-five patients with confirmed GD were included. Diagnosis was confirmed by reduced β-glucosidase, glucocerebrosidase enzyme activity, and supported by elevated plasma chitotriosidase activity. The entire coding region of GBA1 was analyzed using bidirectional Sanger sequencing. Results: Among 45 patients from 38 unrelated families, 15 variants were identified in 20 combinations, including 12 missense variants, 2 nonsense variants, 1 frameshift variant, 1 splice-site variant, and 1 recombinant variant. Of the missense variants, 10 were pathogenic, while 2 novel variants (A316L and F477R) were classified as likely pathogenic. The most frequent variants were L444P (28) and N370S (19). The N370S variant was predominant in GD type 1 (19), whereas L444P occurred in both type 1 (15) and type 3 (11) disease. Conclusions: This study demonstrated that 28 of 45 patients with GD in the Republic of Kazakhstan have type 1 disease, with the N370S mutation being the predominant genetic variant (28). Among the 17 patients with type 2 and 3 GD who had central nervous system involvement, the most frequent finding was the L444P mutation.